Microtubule modifications and stability are altered by cilia perturbation and in cystic kidney disease 1. Issue 1 (8th November 2012) - Berbari, Nicolas F.; Sharma, Neeraj; Malarkey, Erik B.; Pieczynski, Jay N.; Boddu, Ravindra; Gaertig, Jacek; Guay‐Woodford, Lisa; Yoder, Bradley K.
Abstract Disruption of the primary cilium is associated with a growing number of human diseases collectively termed ciliopathies. Ciliopathies present with a broad range of clinical features consistent with the near ubiquitous nature of the organelle and its role in diverse signaling pathways throughout development and adult homeostasis. The clinical features associated with cilia dysfunction can include such phenotypes as polycystic kidneys, skeletal abnormalities, blindness, anosmia, and obesity. Although the clinical relevance of the primary cilium is evident, the effects that cilia dysfunction has on the cell and how this contributes to disease remains poorly understood. Here, we show that loss of ciliogenesis genes such as Ift88 and Kif3a lead to increases in post‐translational modifications on cytosolic microtubules. This effect was observed in cilia mutant kidney cells grown in vitro and in vivo in cystic kidneys. The hyper‐acetylation of microtubules resulting from cilia loss is associated with both altered microtubule stability and increased α‐tubulin acetyl‐transferase activity. Intriguingly, the effect on microtubules was also evident in renal samples from patients with autosomal recessive polycystic kidneys. These findings indicate that altered microtubule post‐translational modifications may influence some of the phenotypes observed in ciliopathies. © 2012 Wiley Periodicals, Inc